PELAKSANAAN PERATURAN KEWAJIBAN SERTIFIKASI HALAL TERHADAP DEPOT AIR MINUM ISI ULANG DI KECAMATAN PAYAKUMBUH BARAT BERDASARKAN UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Muhammad Septiardana; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Based on the explanation in Article 4 of the Law of the Republic ofIndonesia Number 33 of 2014 concerning Halal Product Guarantee explains that"Products that enter, circulate, and are traded in the territory of Indonesia mustbe certified halal". But in reality in the field and in everyday life there are stillmany products circulating in the territory of Indonesia that do not have a halalcertificate and do not implement these rules, especially at the Drinking WaterDepot in West Payakumbuh District. From the explanation above, the authorraises the formulation of the problem, namely, how is the implementation of halalcertification for refill drinking water depots based on Law Number 33 of 2014concerning Halal Product Guarantee and what are the obstacle factors forbusiness actors for refill drinking water depots in West Payakumbuh District inthe certification process Halal and the implementation of Halal Certification bythe Indonesian Ulema Council of Payakumbuh City.This research is classified in the type of research using the juridicalempirical research method, the approach used is sociological juridical, because itdirectly conducts research on the location or point being examined to provide acomplete and clear picture of the problem being examined, while the samplepopulation is all parties involved. with the problems studied in this study, the datasources used, primary data and secondary data, data collection techniques in theresearcher. This research was conducted at the Indonesian Ulema Council inPayakumbuh City and a refill drinking water depot in West Payakumbuh District.The purpose of this study was to determine the process of halal certification andthe obstacles and efforts to implement halal certification.The results of theresearch and the conclusions of the researchers are as follows: First, it ismandatory for all those who trade in the territory of Indonesia to have a halalcertificate.Keywords: Halal Certification, Drinking Water Depot, Indonesian UlemaCouncil.